Dampak Luas Lahan terhadap Kinerja Usahatani Cabai Merah (Kasus Provinsi Sumatera Utara) - Yolanda D. S. Saragih; Rachmat Pambudy; Triana Gita Dewi (JIA (Jurnal Ilmiah Agribisnis) : Jurnal Agribisnis dan Ilmu Sosial Ekonomi Pertanian, 2023)
One of the production centers for red chili papers is North Sumatra Province. On the other hand, North Sumatra is one of the provinces that underwent agricultural land conversion. This study aims to examine how the size of the farm's land affects the farm performance of the red chili pepper crop in North Sumatra, measured by revenue, cost, income, and efficiency. The study was conducted in 2022–2023 using data from 1.876 farmers and secondary data from SHR2014 and BPS. The study employs two main research methods: (1) an analysis of revenue, cost, income, and revenue of cost ratio and (2) the use of the Kruskal-Wallis test to determine the impact of land size on farm performance. According to this study, the small-sized land farmers generate the highest total cost, and the large-sized land farmers use the lowest cost of production. On the other hand, the total revenue produced by small-sized land farmers has the highest cost, and the large-sized land farmers generate the lowest total revenue. Income calculation stated that small land farmers get the smallest income on cash cost, and large land farmers generate the most significant income. Thus, large land farmers achieve the highest revenue-of-cost ratio. According to the Kruskall-Wallis test, the land size affects the following: revenue, cost, income, and revenue of cost ratio. Consequently, it may be said that land area impacts the performance of red chili pepper farms.